Restoration of a boreal peatland impacted by an in‐situ oil sands well‐pad 2: Greenhouse gas exchange dynamics. Issue 3 (7th September 2021) - Engering, Alexandra; Davidson, Scott J.; Xu, Bin; Bird, Melanie; Rochefort, Line; Strack, Maria
Abstract : Across Canada's boreal forest, disturbances from in situ oil sands mining, including well‐pads, significantly impact vast areas of the landscape. The creation of well‐pads requires removal of vegetation and placement of mineral fill, which essentially stops any carbon (C) sequestration on the once peatland ecosystem. It is important that, once no longer in use, these well‐pads are restored as long‐term C (peat) accumulation is what defines peatland ecosystem. However, little is known about the recovery of greenhouse gas exchange post‐restoration of these features. We studied a decommissioned well‐pad located in a treed poor fen that was restored using three soil adjustment treatments (SATs): (1) complete mineral fill removal (Peat‐Dec); (2) partial pad removal and burial under peat layer (BUPL); and (3) mixing mineral and peat by inversion (Mixed‐P‐M). The recreated peat surface was revegetated with donor peatland species using the moss layer transfer technique (MLTT). The objectives of this paper were to (1) quantify plot‐scale seasonal carbon dioxide (CO2 ) and methane (CH4 ) exchange of the SATs, 2–4 years post‐restoration compared to reference sites and (2) determine the influence of several environmental variables on CO2 and CH4 exchange. All SATs proved effective in recreating a soil surface needed to support peatland vegetation as shown by similar rates of net ecosystem exchange (NEE). Equally, both types of vegetation reintroduced led this site on a trajectory toward functioning as a net C sink.